1982
DOI: 10.1021/bi00267a010
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of glycosaminoglycans by thymic lymphocytes. Effects of mitogenic activation

Abstract: The immune response is regulated by cellular interactions involving thymus-derived lymphocytes. Even though evidence from several systems suggests that proteoglycans or their polysaccharide side chains, the glycosaminoglycans, are important mediators (modulators) of cellular interactions, little is known concerning the biosynthesis or possible functions of these macromolecules in lymphocytes. As an initial step in our systematic analyses of the complex arrays of protein saccharides of lymphocytes, the biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 65 publications
(80 reference statements)
4
15
0
Order By: Relevance
“…Another noteworthy finding in the experiment is that peritoneal PMN leucocytes have greatly accelerated secretion of chondroitin 6-sulphate. This result conformed to the observation that glycosaminoglycans synthesized in mitogenically activated lymphocytes are different from those synthesized in non-stimulated cells (Hart, 1982); activated lymphocytes have accelerated secretion of glycosaminoglycans, which appear to be more highly sulphated than those of non-stimulated cells, and to be increased in the relative proportion of both cell-associated and cell-secreted chondroitin 6-sulphate in the total glycosaminoglycans. Furthermore, Vannucchi et al (1982) reported a change in the glycosaminoglycans involved in the activation of PMN leucocytes in adhesion culture.…”
Section: Descending Paper Chromatographysupporting
confidence: 86%
“…Another noteworthy finding in the experiment is that peritoneal PMN leucocytes have greatly accelerated secretion of chondroitin 6-sulphate. This result conformed to the observation that glycosaminoglycans synthesized in mitogenically activated lymphocytes are different from those synthesized in non-stimulated cells (Hart, 1982); activated lymphocytes have accelerated secretion of glycosaminoglycans, which appear to be more highly sulphated than those of non-stimulated cells, and to be increased in the relative proportion of both cell-associated and cell-secreted chondroitin 6-sulphate in the total glycosaminoglycans. Furthermore, Vannucchi et al (1982) reported a change in the glycosaminoglycans involved in the activation of PMN leucocytes in adhesion culture.…”
Section: Descending Paper Chromatographysupporting
confidence: 86%
“…It has been shown that human lymphocytes and monocytes produce various PG types (Kolset et al, 1983(Kolset et al, , 1984. Normal T-and B-lymphocytes predominantly synthesize CSPGs (Morris et al, 1989;McQuillan et al, 1989;Levitt and Ho, 1983) as well as HSPGs (25% of total PGs; Levitt and Ho, 1983;Wilson and Rider, 1991;Hart, 1982). Steward et al (1990) demonstrated that T-cells secrete CS chains to culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…Mitogenic substances has been reported to affect proliferation of leukemic cells of T, B and monocytic origin (Weiss et al, 1986;Papadogiannakis et al, 1986;Hart, 1982;Hadden, 1988). In the present work, their effect on the synthesis and distribution of GAGs, independently of cell proliferation, was studied.…”
Section: Discussionmentioning
confidence: 88%
“…Normal T and B lymphocytes predominantly synthesize CSPGs (Morris et al, 1989;McQuillan et al, 1989;Levitt and Ho, 1983) as well as HSPGs (Levitt and Ho, 1983;Wilson and Rider, 1991;Hart 1982). T lymphocytes secrete mainly 4-sulfated, CSPGs chains to culture medium (Steward et al, 1990), whereas B lymphocytes synthesize both 4-sulfated PGs and 6-sulfated CSPGs (Rider and Hart, 1987).…”
Section: Introductionmentioning
confidence: 99%